METHODS OF AUTOMATIC QUALITY CONTROL OF AGGLUTINANTSANDS IN FOUNDRY - D. M. Kukuj; S. L. Rovin; M. A. Saikov (Литьë и металлургия)
The article is dedicated to comparative analysis of the well-known methods of automatic quality control of agglutinant sands in process of their preparation and to the problems of automation control of the mix preparation processes.